Freud, la répétition et les figures de la hantise pulsionnelle - Claire Pagès (Conserveries Mémorielles)
Despite Freud’s rationalist rejection of the obsession as supernatural phenomenon, we propose to demonstrate that there is a great theory of instinctual obsession in freudian psychoanalysis. This one has a specific framwork : the conservation in the unconscious of all repressed psychic contents and the phenomenon of the return of the repressed. The various figures of the instinctual obsessive fear are all figures of repetition. The problem is that of whether Freud conceives a radical or pure form of obsession, that is to say a figure of repetition without any profit, a completly alienating repetition.